1989
DOI: 10.1111/j.1469-8749.1989.tb04030.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Vision Ads for Preschool Children

Abstract: SUMMARY A study was made of the use of low vision aids to augment the vision of children with very severe visual disability. This paper reports the results for 28 children, using a ‘lobster pot’ stand magnifier, 26 of whom were aged between 18 and 60 months. Success was evaluated by measuring functional vision for nursery‐age learning material in aided and unaided conditions. Half the children showed improved functional vision and one‐third retained the magnifier for continued use. The influence of visual powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 6 publications
0
20
0
2
Order By: Relevance
“…Such a perception–action organization is what low‐vision professionals often label as viewing behaviour , a term as yet without a clear definition. The quality of the viewing behaviour is what ultimately determines a child’s functional vision 7 . In conclusion, more insight into the perception–action organization that underlies viewing behaviour, and its development in young children with visual impairments, is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a perception–action organization is what low‐vision professionals often label as viewing behaviour , a term as yet without a clear definition. The quality of the viewing behaviour is what ultimately determines a child’s functional vision 7 . In conclusion, more insight into the perception–action organization that underlies viewing behaviour, and its development in young children with visual impairments, is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…As an exception, in an experiment by Ritchie et al, 7 visually impaired children aged 18 months to 5 years had to name pictures and small objects with and without the help of a stand magnifier on two occasions. Results revealed an improvement in functional vision (i.e.…”
Section: A Measure Of the Effectiveness Of A Low‐vision Aid For Youngmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the effect of low vision aids was assessed among preschool children; and after 2 years, it was found that 50% of the children remained users of both far vision and near vision aids, with improvement of visual function. The lower degree of compliance in this study may have been, related to the lack of interest in reading and visualizing far objects in pre-school children 19. A limitation of this study was the use of a non validated questionnaire to obtain feedback.…”
Section: Discussionmentioning
confidence: 85%
“…There are developmental, psychosocial, and physical-motor advantages for children receiving early intervention. Psychosocially it has been shown that the earlier in life a child is exposed to assistive devices, such as magnifiers and telescopes, the more likely they are to accept device usage without fear of being "different" from their peers (Ritchie et al 1989). For example, a very young child may accept any device that will enable them to perform a desired task, such as spotting a map on the back of a cereal box.…”
Section: Early Interventionmentioning
confidence: 98%